Flow-Performance Relationship and Tournament Behavior in the Mutual Fund Industry - MA, Baoling (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we interpret the flow-performance relationship as an incentive scheme implicitly given to mutual fund managers by mutual fund investors. We show that the flow-performance relationship varies not only with economic activity but also across fund attributes. We provide evidence that the degree of convexity of the flow-performance relationship has a positive effect on the magnitude of tournament behavior. Different from the conventional tournament hypothesis, we show that although the convexity of the flow-performance relationship does produce implicit incentives for fund managers to modify risk-taking behavior as a function of their prior performance, whether or not the mid-year losers increase the risk of their portfolios highly depends on the convexity degree of the flow-performance relationship.